Loneliness and psychological well-being among adolescents K-Pop fans - Fauziyah, Luthfiana Nur; Widiana, Herlina Siwi; Widyowati, Arini (Universitas Ahmad Dahlan, 2023)
Psychological well-being is important for adolescent, especially on their mental health. This study aimed to examine the relationship between loneliness and psychological well-being in adolescent K-pop fans. The population in this study were adolescents aged 13-18 years who were K-pop fans, with a research sample obtained from quota sampling with a total of 100 people. This research applied the quantitative method, while the data collection tools included the psychological well-being and loneliness scales. The data are then analyzed using the product moment technique. The study results show a significant negative relationship between loneliness and psychological well-being among adolescent K-pop fans. The level of psychological well-being and loneliness adolescent K-pop fans are in the moderate category. Based on the study results, the lower the level of loneliness among adolescents, the higher the psychological well-being will be and vice versa. The higher the level of loneliness, the lower the psychological well-being.